2020
DOI: 10.1371/journal.pone.0237938
|View full text |Cite
|
Sign up to set email alerts
|

Role of e-cigarettes and pharmacotherapy during attempts to quit cigarette smoking: The PATH Study 2013-16

Abstract: Background More smokers report using e-cigarettes to help them quit than FDA-approved pharmacotherapy. Objective To assess the association of e-cigarettes with future abstinence from cigarette and tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 36 publications
1
51
1
1
Order By: Relevance
“…Most notably, the study provided behavioral support to participants in both arms, which, although best practice, is not used by the majority of people trying to quit smoking (Shiffman et al 2008). The results of this study conflict with earlier findings (Kalkhoran and Glantz 2016), and two more recent U.S. studies using longitudinal survey data from the Population Assessment of Tobacco and Health (PATH) concluded that in realworld settings, those using e-cigarettes to assist in smoking cessation were no more likely to succeed than those using NRT (Chen et al 2020;Pierce et al 2020).…”
Section: Statistic 2: Nearly Twice As Effective As Nrtcontrasting
confidence: 85%
“…Most notably, the study provided behavioral support to participants in both arms, which, although best practice, is not used by the majority of people trying to quit smoking (Shiffman et al 2008). The results of this study conflict with earlier findings (Kalkhoran and Glantz 2016), and two more recent U.S. studies using longitudinal survey data from the Population Assessment of Tobacco and Health (PATH) concluded that in realworld settings, those using e-cigarettes to assist in smoking cessation were no more likely to succeed than those using NRT (Chen et al 2020;Pierce et al 2020).…”
Section: Statistic 2: Nearly Twice As Effective As Nrtcontrasting
confidence: 85%
“…A recent publication by Glasser et al 1 reports a series of analyses on the associations of e-cigarette use and cigarette abstinence. Of interest, the two senior authors were also co-authors on another recent publication 2 reporting on e-cigarette use and cigarette abstinence that came to a strikingly different conclusion, despite using the same data set from the Population Assessment of Tobacco and Health (PATH) cohort study.…”
mentioning
confidence: 99%
“…For instance, one study found that e-cigarettes are effective for smoking cessation in young adults with high nicotine dependence levels ( Selya et al, 2018 ). Two other studies found that e-cigarettes have similar smoking cessation effectiveness to not using any products or using conventional pharmacotherapy after 1–2 years of abstinence ( Weaver et al, 2018 , Pierce et al, 2020 ). A fourth found that hospital patients using e-cigarettes have less success with smoking abstinence compared to non-users after 6 months ( Rigotti et al, 2018 ).…”
Section: Is Vaping a Viable Smoking Cessation Aid?mentioning
confidence: 97%